Patriarchy and Its Impacts on Women in Laila Lalami’s Hope and Other Dangerous Pursuits: A Feminist Perspective - Shadrina, Mazaya Nur; Andini Suandi Putri; Dina Rosalina (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
This study examines the representation of patriarchy and its impacts on women in Laila Lalami’s Hope and Other Dangerous Pursuits from a feminist literary perspective. Patriarchy is understood as a social system that institutionalizes male dominance and produces various forms of gender injustice, including subordination, marginalization, violence, and restricted female agency. Using a qualitative textual analysis grounded in feminist literary criticism, this research analyzes selected narrative passages, characterizations, and dialogues to reveal how patriarchal structures operate within the novel and shape the lived experiences of female characters. The findings show that patriarchy manifests primarily through domestic control, male authority, and gender-based violence, particularly in the lives of characters such as Noura, Halima, and Faten. However, the novel also portrays women’s resistance to patriarchal domination through everyday strategies of negotiation, endurance, and self-determination. These acts of resistance function as counter-narratives that challenge patriarchal norms and complicate representations of Muslim women as passive victims. This study contributes to feminist literary scholarship by demonstrating how Hope and Other Dangerous Pursuits not only exposes the oppressive effects of patriarchy but also foregrounds women’s agency within constraining sociocultural contexts.